2017
DOI: 10.1001/jama.2016.19976
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous Glucose Monitoring vs Conventional Therapy for Glycemic Control in Adults With Type 1 Diabetes Treated With Multiple Daily Insulin Injections

Abstract: IMPORTANCEThe majority of individuals with type 1 diabetes do not meet recommended glycemic targets.OBJECTIVE To evaluate the effects of continuous glucose monitoring in adults with type 1 diabetes treated with multiple daily insulin injections. DESIGN, SETTING, AND PARTICIPANTSOpen-label crossover randomized clinical trial conducted in 15 diabetes outpatient clinics in Sweden between February 24, 2014, and June 1, 2016 that included 161 individuals with type 1 diabetes and hemoglobin A 1c (HbA 1c ) of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
481
3
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 581 publications
(562 citation statements)
references
References 38 publications
28
481
3
15
Order By: Relevance
“…The Diamond trial 32 demonstrated a significantly greater (0.6%) decrease in HbA1c and time in hypoglycemia (43 vs. 80 min/day) with the use of CGM plus individualized insulin dosing recommendations. The 1-year duration GOLD trial 33 used a crossover design and demonstrated slightly lower (0.43%) HbA1c levels with CGM and significant education. This effect disappeared in subjects using CGM <70% of the time.…”
Section: Recent Clinical Trialsmentioning
confidence: 99%
“…The Diamond trial 32 demonstrated a significantly greater (0.6%) decrease in HbA1c and time in hypoglycemia (43 vs. 80 min/day) with the use of CGM plus individualized insulin dosing recommendations. The 1-year duration GOLD trial 33 used a crossover design and demonstrated slightly lower (0.43%) HbA1c levels with CGM and significant education. This effect disappeared in subjects using CGM <70% of the time.…”
Section: Recent Clinical Trialsmentioning
confidence: 99%
“…From a baseline HbA1c of 8.6%, the mean HbA1c during CGM use was 7.92%, and during conventional treatment was 8.35%, mean difference -0.43% (95% CI -0.57% to -0.29%, P < 0.001). 43 Time spent in hypoglycemia was 2.79% during the CGM period and 4.79% during conventional therapy. 43 Notably, significant improvement was noted in subjective wellbeing and treatment satisfaction, and hypoglycemia confidence improved during the CGM treatment period in GOLD.…”
Section: Impact Of Cgm On Hypoglycemia and Hypoglycemia Unawarenessmentioning
confidence: 95%
“…43 Time spent in hypoglycemia was 2.79% during the CGM period and 4.79% during conventional therapy. 43 Notably, significant improvement was noted in subjective wellbeing and treatment satisfaction, and hypoglycemia confidence improved during the CGM treatment period in GOLD. 43 The conclusions drawn from these studies were summarized by Davidson 44 As the prevalence of type 1 diabetes increases, clinicians and healthcare systems will be challenged to find better management strategies that are patient centric, and that reduce both the acute and chronic risks of the disease.…”
Section: Impact Of Cgm On Hypoglycemia and Hypoglycemia Unawarenessmentioning
confidence: 95%
See 2 more Smart Citations